Agricultural Communicators in Education - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1980)
Editorial back matter for vol. 64, no.2, April-June (1980) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education